From source to sea: Floating macroplastic transport along the Rhine river - Kuizenga, Boaz; Tasseron, Paolo F.; Wendt-Potthoff, Katrin; van Emmerik, Tim H. M. (Frontiers in Environmental Science, 2023)
Rivers are pathways and storage zones for plastic pollution. Land-based plastic waste enters river systems through anthropogenic and hydrometeorological processes, after which they are transported and retained. Only a small fraction (<2%) is assumed to make it into the ocean. Understanding and quantifying river plastic transport are important to optimize prevention and reduction strategies and to evaluate the efficacy of new regulations and interventions. To achieve this, consistent and reliable data are crucial. River plastic pollution monitoring is still an emerging field, especially since river-scale plastic pollution assessments are limited to date. Here, we present an estimate of floating plastic transport and polymer characterization along the Rhine, from Switzerland to the river mouth in the Netherlands. We show plastic transport is highly variable along the river, but with a significant increase towards the river mouth. High plastic transport was observed close to urban areas, and confluences with tributaries, suggesting both are likely entry points of plastic pollution. The largest plastic transport was measured in the estuary, which is explained by the tidal dynamics, limiting the transport of plastic into the sea. Our results can be used as a baseline to compare with future assessments. Furthermore, the plastic transport and composition estimates can be directly compared to other rivers that applied the same approach, which may reduce the uncertainty in global river plastic emission simulations. With our study, we aim to contribute to the development of a simple harmonized plastic monitoring approach to quantify plastic pollution at the river basin scale.